Anti-diarrhoeal and CNS Depressant Activity of Methanolic Extract of Saccharum spontaneum Linn. (Stamford Journal of Pharmaceutical Sciences, 2009)
Preliminary phytochemical screening of the methanolic extract of the whole plant of Saccharum spontaneum Linn. (Family- Gramineae) revealed the presence of alkaloids, flavonoids, reducing sugar, tannins and saponins. The antidiarrhoeal activity of the extract (200 and 400 mg/kg) was assessed on experimental animal and a dose dependent decrease in the total number of faecal dropping was obsereved in castor oil induced diarrhoea in mice. The plant extract was also assessed for effect on the central nervous system (CNS) using a number of neuropharmacological experimental models in mice. The extract produced a dosedependent reduction of the onset and duration of pentobarbitone-induced hypnosis, reduction of locomotor and exploratory activities in the open field and hole cross tests. These results suggest that the extract possesses antidiarrhoeal and CNS depressant activity. Key Words: Saccharum spontaneum, Castor oil, Loperamide, Pentobarbitone. doi:10.3329/sjps.v1i1.1810 S. J. Pharm. Sci. 1(1&2): 63-68